Strategi Pengembangan Sumberdaya Manusia Dalam Meningkatkan Kinerja Aparatur Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Sarmi - Sidwas Muarsarsar (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
Strategies that can be carried out by organizations in improving the performance of their apparatus/employees include increasing human resource development. The purpose of this study was to identify and analyze human resource development strategies, supporting and inhibiting factors of human resource development strategies in improving the performance of the apparatus at the Agency for Personnel and Human Resources Development in Sarmi Regency. The research method uses a qualitative approach, data collection techniques are observation, interviews, and documentation. The results of this study are: 1) The strategy for developing human resources at the BKPSDM in Sarmi Regency has not run optimally and effectively based on the findings, as follows: a) Increasing the development of the apparatus formally and informally is not good b) Increasing the career development of the apparatus, namely providing promotions to employees who excel, not well implemented, c) Improvement of the Merit System in Employee Management, namely placing employees according to the field and background of the employee's discipline is lacking well implemented 2) Supporting and inhibiting factors (a) Supporting factors: Availability of legal protection, external support such as Corporate Social Responsibility assistance or scholarships, availability of training institutions, educational institutions, availability of budgetary resources, human resources, and facilities (b) Inhibiting factors: limited budget, limited personnel/human resources, supporting facilities for human resource development are limited and inadequate, weak supervision, low level of employee welfare.